PENGARUH CAUSE-RELATED MARKETING DAN PROMOSI PENJUALAN TRADISIONAL PADA NIAT KONSUMEN UNTUK LOYAL TERHADAP MEREK YANG DIMODERASI OLEH KETERLIBATAN KONSUMEN TERHADAP PRODUK - , Dwi Asri Siti Ambarwati ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Cause Related Marketing is a part of corporate responsibility that directly relates with sales, where a company that is partnered with a nonprofit organization, creates a mutually beneficial relationship in order to increase sales of certain products and to obtain financial support for charity. The hypothesis in this thesis was that Cause Related Marketing (CRM) would have an influence on consumer intention to be loyal to the brand. In this case, consumer intention to be loyal to the brand had four stages as follow: cognitive loyalty, affective loyalty, conative loyalty and behavior loyalty. In this research, CRM campaign would be compared with the traditional sales promotion in the form of lottery promotion, based on its influence on consumer intention to be loyal to the brand. This was due to the traditional sales promotion in the context of Indonesia was still more popular than the CRM campaign itself. The influence of CRM and traditional sales promotion on consumer intention to be loyal to the brand would be moderated by the involvement of consumers to the product. This was important because the type of product being marketed defined consumer's perception in appreciating a company's marketing strategy. The involvement of consumers to the product was categorized into: low involvement and high involvement. The involvement was low when the consumer had a little of considerations in buying the product and the involvement would be high when the consumer had a lot of considerations when buying the product. The research design used in this study was experimental design. The variables manipulated in this experiment were CRM campaign and traditional sales promotion on two products which had high consumer involvement (expensive and high quality laptop bag) and low consumer involvement (cheap laptop bag with medium quality), with under graduate student at University of Lampung as the participants. After that, the hypothesis was examined using one-way ANOVA and two way ANOVA analysis. The result of hypothesis examination indicated that strategic CRM campaign and traditional sales promotion had influences on consumer intention to be loyal to the brand. Result from one way ANOVA test showed that the influence of strategic CRM campaigns on consumer intention to be loyal to the brand was greater than the influence of the traditional sales promotion. The experiment using two way ANOVA to examine the influence of moderation on type of product with high involvement and low involvement indicated that the involvement of consumers to the products indeed moderated the influence of strategic CRM campaign and traditional sales promotion on consumer intention to be loyal to the brand.